2011
DOI: 10.1007/s10646-011-0731-0
|View full text |Cite
|
Sign up to set email alerts
|

Great Lakes fish consumption advisories: is mercury a concern?

Abstract: The majority of the restrictive fish consumption advisories for the Canadian waters of the Great Lakes issued by the Ontario Ministry of the Environment, Canada based on the most restrictive contaminant, are attributed to polychlorinated biphenyls (PCBs) and dioxins/furans. Mercury currently causes about <1-2.5% and 9-16% of the restrictive advisories for the general population (GP) and sensitive population of children under 15 and women of child-bearing age (SP), respectively (the St. Lawrence River is not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Levels of various contaminants have been monitored in Ontario fish since the 1970s through Sport Fish Contaminant Monitoring Program of Ontario Ministry of the Environment and Climate Change (OMOECC). 18 The monitoring data generated by the program include 1151 fish samples measured for 56 PCB congeners. After excluding 112 samples with all major PCB congeners below their detection limits, the final data set included 572 skinless, boneless fillet (SBF) samples of 25 sport fish species from 51 locations, 22 whole body fish composite (WFC) samples of two forage fish species from one location, and 445 young-of-the-year whole body fish composite (YFC) samples of 11 fish species from 60 locations (Supporting Information (SI) Table S1a).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Levels of various contaminants have been monitored in Ontario fish since the 1970s through Sport Fish Contaminant Monitoring Program of Ontario Ministry of the Environment and Climate Change (OMOECC). 18 The monitoring data generated by the program include 1151 fish samples measured for 56 PCB congeners. After excluding 112 samples with all major PCB congeners below their detection limits, the final data set included 572 skinless, boneless fillet (SBF) samples of 25 sport fish species from 51 locations, 22 whole body fish composite (WFC) samples of two forage fish species from one location, and 445 young-of-the-year whole body fish composite (YFC) samples of 11 fish species from 60 locations (Supporting Information (SI) Table S1a).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Feather mercury concentrations in nestlings declined by nearly 80% from 1989 to 2010, a trend attributed to a lake-level stabilization order by the International Joint Commission that was implemented in 1999. Interestingly, as observed in some fish populations (Monson 2009;Monson et al 2011;Bhavsar et al 2011;Zananski et al 2011), there appears to be a biphasic response in nestling mercury concentrations with increasing concentrations observed over the period spanning 2000-2010.…”
Section: Spatial Patterns and Mercury Accumulation In Fish And Wildlifementioning
confidence: 57%
“…Sandheinrich et al (2011) examined the proportion of predatory fish that were predicted to be at risk from high concentrations of mercury and found that most fish at risk were in inland lakes and impoundments, whereas no sites in the Great Lakes had fish exceeding threshold concentrations for adverse effects. Bhavsar et al (2011), who examined consumption advisories in the Canadian waters of the Great Lakes, found that only \1-2.5% of present restrictive advisories for the general population and 9-16% for the sensitive population were due to mercury. If other contaminants were not a factor, mercury in fishes from Canadian waters of the Great Lakes was considered to be of minor concern for the general population and of moderate concern for sensitive populations.…”
Section: Spatial Patterns and Mercury Accumulation In Fish And Wildlifementioning
confidence: 99%
“…However, the same person can consume only 2.7, 1.5 and 0.9 kg of the respective fishes per week to not exceed the 0.7 µg/kg body weight limit proposed by the US-NCR. The government should be responsible for obtaining information on the availability and contaminant levels for commonly eaten fish species so as to allow people to make informed decisions about the health risks from fish consumption [16,28]. Sometimes the people are compelled to choose chemical risk rather than giving up the consumption of contaminated fish due to their cultural and religious beliefs [25].…”
Section: Resultsmentioning
confidence: 99%
“…Since the main susceptible groups for Hg poisoning are growing fetus and growing children ( i.e ., undergoing brain development), women of reproductive age and small children are regarded as the most susceptible targets to Hg poisoning [15,16,17,18,19]. It has been proven that Hg is bound to proteins such as muscle, which is the main edible part of fishes, and its levels there cannot be reduced or removed by cooking [20].…”
Section: Introductionmentioning
confidence: 99%